THE ROLE OF INTERNAL COMMUNICATION IN BUILDING A SOLID WORK TEAM AT BUMDES (VILLAGE-OWNED ENTERPRISES) - Eli Suherli; Sidik Budiwidodo; Farika Chandrasari; Agus Rohmat Hidayat (Politeknik Siber Cerdika Internasional, 2024)
Effective internal communication is one of the key factors in building a solid work team in Village-Owned Enterprises (BUMDes). This study aims to explore the role of internal communication in shaping team cohesion in BUMDes, as well as its impact on organizational performance. Using a descriptive qualitative approach, data was obtained through in-depth interviews and participatory observations with BUMDes managers and staff in several villages. The results show that open and transparent communication between managers and team members is highly influential in improving coordination, resolving problems, and strengthening collective work spirit. In addition, a clear understanding of the objectives and roles of each member also supports the creation of a harmonious working environment. This research contributes to the development of more effective communication strategies in the context of village-based organizations, and offers practical recommendations for BUMDes managers to improve the quality of internal communication in an effort to strengthen village economic institutions.